Chikungunya virus requires an intact microtubule network for efficient viral genome delivery. - Tabitha E Hoornweg; Ellen M Bouma; Denise P I van de Pol; Izabela A Rodenhuis-Zybert; Jolanda M Smit (Public Library of Science (PLoS), 2020)
Chikungunya virus (CHIKV) is a re-emerging mosquito-borne alphavirus, which has rapidly spread around the globe thereby causing millions of infections. CHIKV is an enveloped virus belonging to the Togaviridae family and enters its host cell primarily via clathrin-mediated endocytosis. Upon internalization, the endocytic vesicle containing the virus particle moves through the cell and delivers the virus to early endosomes where membrane fusion is observed. Thereafter, the nucleocapsid dissociates and the viral RNA is translated into proteins. In this study, we examined the importance of the microtubule network during the early steps of infection and dissected the intracellular trafficking behavior of CHIKV particles during cell entry. We observed two distinct CHIKV intracellular trafficking patterns prior to membrane hemifusion. Whereas half of the CHIKV virions remained static during cell entry and fused in the cell periphery, the other half showed fast-directed microtubule-dependent movement prior to delivery to Rab5-positive early endosomes and predominantly fused in the perinuclear region of the cell. Disruption of the microtubule network reduced the number of infected cells. At these conditions, membrane hemifusion activity was not affected yet fusion was restricted to the cell periphery. Furthermore, follow-up experiments revealed that disruption of the microtubule network impairs the delivery of the viral genome to the cell cytosol. We therefore hypothesize that microtubules may direct the particle to a cellular location that is beneficial for establishing infection or aids in nucleocapsid uncoating.